Twenty-first century response of Petermann Glacier, northwest Greenland to ice shelf loss - Hill, Emily; Gudmundsson, Hilmar; Carr, Rachel; Stokes, Chris R.; King, Helen (Journal of Glaciology, 2021)
Ice shelves restrain flow from the Greenland and Antarctic ice sheets. Climate-ocean warming could force thinning or collapse of floating ice shelves and subsequently accelerate flow, increase ice discharge, and raise global mean sea levels. Petermann Glacier (PG), northwest Greenland, recently lost large sections of its ice shelf, but its response to total ice shelf loss in the future remains uncertain. Here, we use the ice flow model Úa to assess the sensitivity of PG to changes in ice shelf extent, and to estimate the resultant loss of grounded ice and contribution to sea level rise. Our results have shown that under several scenarios of ice shelf thinning and retreat, removal of the shelf will not contribute substantially to global mean sea level (< 1 mm). We hypothesise that grounded ice loss was limited by the stabilization of the grounding line at a topographic high approximately 12 km inland of its current grounding line position. Further inland, the likelihood of a narrow fjord that slopes seawards suggests that PG is likely to remain insensitive to terminus changes in the near future.